Intracellular trafficking of size-tuned nanoparticles for drug delivery - Gimondi, Sara (2024)
Polymeric nanoparticles (NPs) are widely used as drug delivery systems in nanomedicine. Despite their widespread application, a comprehensive understanding of their intracellular trafficking remains elusive. In the present study, we focused on exploring the impact of a 20 nm difference in size on NP performance, including drug delivery capabilities and intracellular trafficking. For that, poly(ethylene glycol) methyl ether-block-poly(lactide-co-glycolide) (PLGA-PEG) NPs with sizes of 50 and 70 nm were precisely tailored. To assess their prowess in encapsulating and releasing therapeutic agents, we have employed doxorubicin (Dox), a well-established anticancer drug widely utilized in clinical settings, as a model drug. Then, the beneficial effect of the developed nanoformulations was evaluated in breast cancer cells. Finally, we performed a semiquantitative analysis of both NPsâ uptake and intracellular localization by immunostaining lysosomes, early endosomes, and recycling endosomes. The results show that the smaller NPs (50 nm) were able to reduce the metabolic activity of cancer cells more efficiently than NPs of 70 nm, in a time and concentration-dependent manner. These findings are corroborated by intracellular trafficking studies that reveal an earlier and higher uptake of NPs, with 50 nm compared to the 70 nm ones, by the breast cancer cells. Consequently, this study demonstrates that NP size, even in small increments, has an important impact on their therapeutic effect.